Cardiac Involvement among HIV-positive Individuals less than 18 years of Age on Antiretroviral Therapy- An Observational Study from a Rural Tertiary Care Hospital, West Bengal, India - Uttam Kumar Sarkar; Indrajit Mandal; Somenath Ganguly; Akash Rai; Kaushik Ishore (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: With advancement of medical science, individuals diagnosed with Human Immunodeficiency Virus (HIV) infections are getting treated earlier and a fewer of them develop Acquired Immunodeficiency Syndrome (AIDS)-related complications. But the downside is that there is an earlier onset and higher relative risks for different chronic diseases including cardiovascular diseases. Aim: To determine the proportion and pattern of cardiac involvements among children undergoing treatment for HIV infection and to correlate various cardiac findings with duration of Antiretroviral Therapy (ART) among them. Materials and Methods: An observational cross-sectional study was conducted among 136 HIV infected patients attending Paediatrics and General Medicine Outpatient Departments of North Bengal Medical College and Hospital (NBMCH) from October 2019 to March 2021. All patients were assessed clinically and underwent two dimensional (2D) echocardiography, Motion mode (M mode) and colour doppler for assessing cardiac involvement. Collected data were analysed using Statistical Package for the Social Sciences (SPSS) software version 22.0 and Pearson's Correlation test was applied to test association between duration of ART and different echocardiographic parameters. Results: The mean age of the study participants was 10.14 years and the mean duration of ART was 49.18 months. Almost half (48.5%) of the HIV-positive individuals had cardiovascular findings. The most common echocardiographic change noted in patients was diastolic dysfunction 39 (28.7%) followed by Pericardial Effusion (PE) 29 (21.3%) and systolic dysfunction 28 (20.6%). Statistically significant positive correlation between changes in the values of Left Ventricular Internal Diameter in Diastole (LVIDD) (r=0.982), Left Atrium (LA) (r=0.634), mean Pulmonary Artery Pressure (mPAP) (r=0.200) with duration of ART was noted. Negative correlation was seen between duration of ART with ejection fraction (r=-0.984) and Tricuspid Annular Plain Systolic Excursion (TAPSE) (r=-0.438). This indicated that all these important cardiological parameters became worser with advancement of treatment. Conclusion: Cardiac involvements among HIV positive individuals undergoing ART were still high. There was definite correlation between cardiac involvement and duration of ART.